2017
DOI: 10.1158/0008-5472.can-17-1355
|View full text |Cite
|
Sign up to set email alerts
|

MRE11 Promotes Tumorigenesis by Facilitating Resistance to Oncogene-Induced Replication Stress

Abstract: Hypomorphic mutations in the genes encoding the MRE11/RAD50/NBS1 (MRN) DNA repair complex lead to cancer-prone syndromes. MRN binds DNA double strand breaks where it functions in repair and triggers cell cycle checkpoints via activation of the ataxia-telangiectasia mutated (ATM) kinase. To gain understanding of MRN in cancer, we engineered mice with B lymphocytes lacking MRN, or harboring MRN in which MRE11 lacks nuclease activities. Both forms of MRN deficiency led to hallmarks of cancer, including oncogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Spehalski et al 46 reported that Mre11 deficiency prevented tumorigenesis in mouse p53 −/− B-cell lymphoma models associated with oncogenic translocations involving Myc genes, indicating that MRE11 (and by extension the MRN complex) cannot be considered a standard tumor suppressor since its activity is required for cancer development. In line with this, we have now demonstrated that MRE11 is also required for an efficient RS control and for the survival of preclinical models of established MYCN-driven human cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spehalski et al 46 reported that Mre11 deficiency prevented tumorigenesis in mouse p53 −/− B-cell lymphoma models associated with oncogenic translocations involving Myc genes, indicating that MRE11 (and by extension the MRN complex) cannot be considered a standard tumor suppressor since its activity is required for cancer development. In line with this, we have now demonstrated that MRE11 is also required for an efficient RS control and for the survival of preclinical models of established MYCN-driven human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that p53 orchestrates DNA replication restart homeostasis via a transcription- and apoptosis-independent function, by aiding MRE11 recruitment on stalled replication forks to prevent the activity of RAD52/Polθ mutagenic pathways 47 . While it is likely that MRE11 recruitment onto “stressed” forks is strictly connected to its tumor survival functions, data from Spehalski et al 46 imply that p53 is dispensable to this end, since they unveiled MRE11 oncogenic activity in p53 − /− B-cell lymphomas. Further studies will be definitely required to better define the complex relationships between p53 and the MRN complex at the replication forks, in normal and cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, 3 genes, MRE11A, TXN and TOP2A , had already been associated with the pathogenesis of lymphoma and, therefore, targeting their expression might be beneficial for tailored therapy ( Online Supplementary Table S3 ). 24 26 …”
Section: Discussionmentioning
confidence: 99%
“…Cancer-related functions of PCBP2, TIA-1, HuR/ELAVL1, SERBP1, YTHDC2, YTHDF2 (Mapofthecell database) were described above. All experimentally defined partners of eEF1Bγ picked up by Cytoscape to build molecular networks, are linked to cancer as well [2,[125][126][127][128][129][130][131][132].…”
Section: Resultsmentioning
confidence: 99%